(untitled) (The International Journal for Scientific Research, 2025)
This study aimed to identify the extent to which faculty members at the Open Arabic University, Sultanate of Oman branch, use digital professional practice communities in their teaching activities, and to achieve the objectives of the study, the descriptive survey approach was followed, where a questionnaire was distributed to a random sample of faculty members, numbering 79 members during the academic year 2023-2024. The results showed that the responses of the sample on the axes of the questionnaire as well as the questionnaire in general were to a large degree, and the study did not show any statistically significant differences in the axes of the questionnaire or in the questionnaire as a whole based on the variable of specialization or experience, however, it was found that there were statistically significant differences between the averages of the participants’ responses based on the degree variable in the axes of obstacles and requirements for employing communities of professional practice, and it was also noted that there was a statistically significant difference in the responses of faculty members in the Employing digital communities of practice in their teaching performance between the "Assistant Professor" and "Professor" categories for the benefit of the "Assistant Professor" category.